Η αναπτυξιακή ψυχολογία ως η πολιτική του ChatGPT για την παιδική ηλικία: ένας θεωρητικός αντίλογος στην Τεχνητή Νοημοσύνη - Κατσιγιάννης, Μιχάλης (Παιδαγωγικά ρεύματα στο Αιγαίο, 2025)
This article will provide a critical presentation and analysis on two axes. First, reference will be made to the two basic – and contrasting – scientific paradigms regarding the study of childhood, developmental psychology on the one hand and the sociology of childhood on the other. Then, I will present the findings that I collected through three discussions with ChatGPT on the issue of childhood, with an additional special interest in the early childhood education. The main conclusion of the article is that ChatGPT reproduces views on childhood which are – mainly – based on developmental psychology.